Time‐dependent density functional theory investigations on structural modification in carbazole‐based organic photosensitizers to improve electron injection in dye‐sensitized solar cell. Issue 15 (22nd April 2020) - Majid, Abdul; Sana, Maryam; Khan, Salah Ud‐Din; Ahmad, Naeem
Abstract: The time‐dependent density functional theory approach, implemented at hybrid‐B3LYP, GGA‐PBE, and density functional‐based tight binding levels of theory, was used to model photoinjection in organic dye/TiO2 quantum dot to explore the prospects of improvement of dye‐sensitized solar cell (DSSC). The photosensitizer used in this study consisted of six carbazole‐based organic dyes, a cyanoacrylic acid group as an acceptor and an oligothiophene π ‐bridge spacer. The modifications were made in the dyes by increasing the length of the spacer by adding thiophene and oxadiazole rings at different positions of the donor‐acceptor bridge. The structural variations appeared to alter the electronic and optical properties of dyes studied via energy levels and excitation spectra. The UV‐Vis spectra calculated for all the dyes in solvents exhibited a red shift in spectral peaks with an increase in the polarity of the solvents. The findings of the study pointed toward the indirect photoinjection of the dye‐(TiO2 )96 complex for six different dyes. The substitution of the oxadiazole ring at the center and addition of a thiophene ring at the edge of the spacer produced two dyes that exhibited the lowest injection energies of 0.11 and 0.17 eV, along with the regeneration energies of 1.18 and 1.12 eV, respectively. The dyes reported here may have promising applications in photoanode for enhancing the performance of DSSC. Abstract : Carbazole is an electron‐rich species, known as organic photoconductor, and acts as a donor in sensitizers, creating photoinjected electrons with a long life by delaying the charge recombination at interfaces. The dyes demonstrated improved the indirect photoinjection in a dye semiconductor system for dye‐sensitized solar cell.